Perilaku Ibu Dalam Pencegahan Stunting Pada BADUTA - Fildzah, Filsya Khoirina; Yamin, Ahmad; Hendrawati, Sri (Jurnal Keperawatan Muhammadiyah, 2020)
The purpose of this research was to identified the behavior of mothers in the prevention of stunting on under two years baby in Cipacing Village, Jatinangor, Sumedang District. This research used quantitative descriptive methods. The population of this study was the mother who had a baby 0-2 years in Cipacing Village, Jatinangor, Sumedang District. The samples in this study were 218 people using proportional stratified random sampling. The data were collected using a likert scaleÂ  questionnaire, analyzed using frequency distribution based on the mean value, then presented in proportion form. The results showed the behavior of mothers in the stunting prevention of 53.07% had good category on stunting prevention behavior, with the highest result was drinking water and household food management sub variable with 74.3% with good categories and the lowest was the hand washing with soap sub variable with a bad behavior category of 55%. The advice for Public Health Center Institution was beside in terms of facilities but also should have a target in improving the behavior of mothers in stunting prevention through STBM-Stunting programs.